2021
DOI: 10.3390/ph14111099
|View full text |Cite
|
Sign up to set email alerts
|

A Rational Design of α-Helix-Shaped Peptides Employing the Hydrogen-Bond Surrogate Approach: A Modulation Strategy for Ras-RasGRF1 Interaction in Neuropsychiatric Disorders

Abstract: In the last two decades, abnormal Ras (rat sarcoma protein)–ERK (extracellular signal-regulated kinase) signalling in the brain has been involved in a variety of neuropsychiatric disorders, including drug addiction, certain forms of intellectual disability, and autism spectrum disorder. Modulation of membrane-receptor-mediated Ras activation has been proposed as a potential target mechanism to attenuate ERK signalling in the brain. Previously, we showed that a cell penetrating peptide, RB3, was able to inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…The analysis of these results suggested that the complex involving PDB 2ZHN and 6MEJ registered a higher number of key interactions between the galectin-9 CRDs and the E2 branched oligosaccharide. Furthermore, in order to explore the contacts between galectin-9 and E2 amino acids, the two MD simulations were processed by clustering the MD frames in 10 clusters per trajectory [ 64 ]. The centroids of each cluster were thus analyzed to deepen the single amino acid role in the complex stabilization ( Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of these results suggested that the complex involving PDB 2ZHN and 6MEJ registered a higher number of key interactions between the galectin-9 CRDs and the E2 branched oligosaccharide. Furthermore, in order to explore the contacts between galectin-9 and E2 amino acids, the two MD simulations were processed by clustering the MD frames in 10 clusters per trajectory [ 64 ]. The centroids of each cluster were thus analyzed to deepen the single amino acid role in the complex stabilization ( Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…77 A panel of HBS-modified peptides were designed and synthesized based on the peptide sequence derived from the α-helix portion of RasGRF1 (Ras guanine nucleotide-releasing factor 1) at the Ras protein binding interface, which showed great potency for inhibiting Ras-RasGRF1 interaction and thus disturbing the downstream signaling pathway implicated in brain disorders. 78 Later, the remarkable efficacy of the HBS strategy was demonstrated by rational design and functional assessment of HBS-stabilized peptides to block the interaction of the p300/CBP coactivator with the transcription factor HIF-1α. 79 In another case, HBS helices that mimic the Bak BH3 domain were demonstrated to target the protein Bcl-xL with high affinities.…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%
“…In 2013, Beard et al demonstrated a correlation between the experimental alanine scanning results and the computational ones obtained though Schrödinger suite. Indeed, a residue can be considered as an interaction hot spot, if its mutation to alanine generates a ∆∆G a nity ≥ 3.0 kcal/mol [44][45][46]. Table 2 lists the ∆∆G a nity values for Hsp70 amino acids registering ∆∆G a nity ≥ 3.0 kcal/mol.…”
Section: Prediction Of Putative Contacts Between Eno1 Key Amino Acids...mentioning
confidence: 99%